The Versatility of the Aryne–Imine–Aryne Coupling for the Synthesis of Acridinium Photocatalysts - Hutskalova, Valeriia; Sparr, Christof (Synlett, 2021)
The increasing use of acridinium photocatalysts as sustainable alternative to precious metal-based counterparts encourages the design and efficient synthesis of distinct catalyst structures. Herein, we report our exploration of the scope of the aryne–imine–aryne coupling reaction combined with a subsequent acridane oxidation for a short two-step approach towards various acridinium salts. The photophysical properties of the novel photocatalysts were investigated and the practical value was demonstrated by a cation-radical accelerated nucleophilic aromatic substitution reaction.
Keywords: acridinium salts; aryne; organocatalysis; photoredox catalysis; synthesis